154 - NEW MANAGEMENT STRATEGIES AND FINANCIAL PERFORMANCE OF FOOTBALL CLUBS IN BRAZIL: AN ANALYSIS FROM OPERATING REVENUES. (Fiep Bulletin - online, 2011)
The aim of this study was to investigate the financial results for Brazilian football clubs who have scheduled management strategies and organization of modern craft. It was, in relation to the objectives of an exploratory study, due to the limited amount of scientific work produced on the subject. The sample consists of two Brazilian teams belonging to Serie A the best performing item in operating income in the balance sheets between 2007 and 2009 - Sao Paulo and Internacional de Porto Alegre. It was concluded that the professional management of the clubs investigated has resulted in the increase of revenue for clubs in the years studied, but still insufficient, because the clubs still have expenses beyond the revenue.